An Exploring Sustainable Tourism Development in Nepal - Kadayat, Giri Raj; Upadhyay, Govinda Raj (AMC Journal (Dhangadhi), 2024)
Nepal, rich in natural and cultural heritage, has significant potential to leverage tourism for economic growth. This research examines the role of tourism as a driver of economic development in Nepal by assessing aspects such as its impact on GDP, generation of foreign exchange earnings, infrastructure development and socio-cultural changes. Through a comprehensive review, presentation of results and evaluation of cases, this article examines the openings and challenges of the tourism industry in Nepal and acknowledges the necessary recommendations to maximize its potential as a healthy and viable financial lever. By focusing on core issues, taking steps towards objective competitiveness and moving forward to strengthen reliable tourism, Nepal can pave the way for today's economic benefits and social development.